The Opinions of the Prospective Science Teachers’ on_x000D_ Structured, Semi-Structured and Unstructured ThreeDimensional Modeling Processes - (:unkn) unknown (My University, 2018)
This research aims to determine the opinions of prospective science teachers regarding structured,semi-structured and unstructured three-dimensional modeling processes according to several problems. Thus,modeling activities were conducted in three different process as structured (problem+materials+process), semistructured (problem+materials) and unstructured (problem). In this research planned within the framework ofembedded multiple case study design, a total number of 67 prospective science teachers created six modelsconcerning human circulation and respiratory system. "Focus Group Discussions," "Video Recordings," and"Model-Related Activity Documents" were used as data collection tools. The collected data were analyzedcomparatively using the content analysis method. Five themes, which are a) challenges encountered, b)contributions, c) availability, d) alternative ideas and e) originality, were found to be common in all modelinggroups. In general, it was determined that modeling activities had some positive impacts such as supportinglearning theoretical information, enabling information to be remembered easily, ensuring the recognition ofincomplete information and learning by doing and supporting learning in a fun environment. As a negativeimpact, on the other hand, it was concluded that it was a hard and tiring task to attach materials during modelingactivities.

Bu araştırmada fen bilgisi öğretmen adaylarının çeşitli problemlere ilişkin farklı modelleme süreçlerine_x000D_ ilişkin görüşlerinin belirlenmesi amaçlanmıştır. Bu doğrultuda modelleme etkinlikleri yapılandırılmış_x000D_ (problem+materyaller+yapılış), yarı-yapılandırılmış (problem+materyaller) ve yapılandırılmamış (problem)_x000D_ olmak üzere üç farklı şekilde yürütülmüştür. İç içe geçmiş çoklu durum deseni çerçevesinde planlanan bu_x000D_ araştırmada toplam 67 fen bilgisi öğretmen adayı insanda solunum ve dolaşım sistemi ünitelerine ilişkin altı_x000D_ model oluşturmuşlardır. Veri toplama araçları olarak “Odak Grup Görüşmesi”, “Video Kayıtları” ve “Modellere_x000D_ Yönelik Etkinlik Dokümanları” kullanılmıştır. Toplanan veriler karşılaştırmalı olarak incelenerek içerik analizi_x000D_ ile analiz edilmiştir. Araştırma sonuçlarına göre bütün modelleme gruplarında ortak olarak karşılaşılan zorluklar,_x000D_ katkıları, kullanılabilirlik, alternatif fikirler ve özgünlük olmak üzere beş tema ortaya çıkmıştır. Genel olarak_x000D_ modelleme aktivitelerinin teorik bilgi öğrenmeyi desteklediği, bilgilerin akılda kalıcı olmasını desteklediği, eksik_x000D_ bilgilerin farkına varılmasını sağladığı, yaparak öğrenmeyi sağladığı ve eğlenceli ortamda öğrenmeyi_x000D_ desteklediği gibi olumlu sonuçların ortak olduğu belirlenmiştir. Olumsuz olarak ise modelleme aktivitelerinde_x000D_ malzemeleri birleştirmenin zor ve yorucu olması dikkat çekici bir sonuç olarak karşımıza çıkmaktadır.
Fen Bilgisi Öğretmen Adaylarının Yapılandırılmış, YarıYapılandırılmış ve Yapılandırılmamış Üç Boyutlu Modelleme Süreçlerine İlişkin Görüşleri